Analisis Determinan Perilaku Etis Auditor (Studi pada Inspektorat Provinsi Papua, Inspektorat Kabupaten Jayapura dan Inspektorat Kota Jayapura) - Salle, Hesty Theresia; Falah, Syaikhul (ITB AAS INDONESIA, 2024)
This study aims to determine the influence of ethical orientation consisting of idealism and relativism as well as equity sensitivity to the ethical behavior of auditors. This type of research is quantitative research with primary data sources and data collection techniques using questionnaires. The study was conducted at the Papua Provincial Inspectorate, Jayapura City Inspectorate and Jayapura Regency Inspectorate as many as 92 respondents. The data analysis used in this study uses the Structural Equation Model (SEM) approach with the Partial Least Square method using PLS 7.0 Wrap Software. The results showed that the variables of ethical orientation of idealism and ethical orientation of relativism had a positive and significant effect on the ethical behavior of auditors, while the variables of equity sensitivity had no effect on the ethical behavior of auditors.